Clinical characteristics of miliary pulmonary metastases in non‐small cell lung cancer - Hanmil Choi; Yunjoo Im; Byeong‐Ho Jeong; Kyungjong Lee; Hojoong Kim; Sang‐Won Um (Thoracic Cancer, 2023)
Abstract Background The prognosis of miliary pulmonary metastases (MPM), which are characterized as randomly disseminated, innumerable, and small metastatic nodules, has been considered as being poor. The purpose of this study was to evaluate the clinical characteristics and survival of MPM in patients with non‐small cell lung cancer (NSCLC). Methods This retrospective study included NSCLC patients with MPM and nonmiliary pulmonary metastases (NMPM) detected during staging evaluation between 2000 and 2020. MPM was defined as >50 bilaterally distributed metastatic pulmonary nodules (<1 cm in diameter), and NMPM was defined as the presence of ≤15 metastatic pulmonary nodules regardless of size. Baseline characteristics, genetic alterations and overall survival (OS) rates were compared between the two groups. Results Twenty‐six patients with MPM and 78 patients with NMPM were analyzed. The median number of patients who smoked was significantly lower in the MPM group than in the NMPM group (0 vs. 8 pack years, p = 0.030). The frequency of EGFR mutation was significantly higher in the MPM group (58%) than in the NMPM group (24%; p = 0.006). There was no significant difference in 5‐year OS between the MPM and the NMPM group by the log‐rank test (p = 0.900). Conclusion MPM in NSCLC were significantly related to EGFR mutation. The OS rate of the MPM group was not inferior to that of the NMPM group. The presence of EGFR mutations should be thoroughly evaluated for NSCLC patients with initial presentation of MPM.